1970
DOI: 10.3329/imcj.v5i2.10097
|View full text |Cite
|
Sign up to set email alerts
|

Trends Of Antibiotic Susceptibility Of Salmonella Enterica Serovar Typhi And Paratyphi In An Urban Hospital Of Dhaka City Over 6 Years Period

Abstract: The antibiotic resistance pattern of salmonella is ever changing over time. The present study is a retrospective analysis of rate of isolation of Salmonella Typhi and Paratyphi and their antibiotic resistance pattern over 6 years period in an urban hospital of Dhaka city. Blood culture submitted in BIRDEM hospital from 2004-2009 were analyzed. Isolated Salmonella sp were identified and antimicrobial susceptibility testing was carried out by a standard disc diffusion method.Among 385 isolated Salmonella sp 304 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…5 Cefixim, ciprofloxacin and levofloxacin were sensitive in significant number of cases, but much lower than previous studies. 11 Nalidixic acid resistance is increasing.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…5 Cefixim, ciprofloxacin and levofloxacin were sensitive in significant number of cases, but much lower than previous studies. 11 Nalidixic acid resistance is increasing.…”
Section: Discussioncontrasting
confidence: 65%
“…Not a single patient was resistant to ceftriaxone in our study although ceftriaxone resistance has been reported from Bangladesh. 5,6 Significant number of patients were resistant to azithromycin as seen in other studies. 10 Its dosing convenience, easy availability and non-judicious use in non-specific febrile illness might be the contributory factor behind it.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations